N-Way Parabolic UWB Planar Spatial Power Divider/Combiner - Yanegh, Ayoub; Ghadimi, Ali; Baladi, Elham (IEEE transactions on microwave theory and techniques, 2025)
In this article, a 1-to-N parabolic ultrawideband (UWB) planar spatial power divider/combiner is designed and implemented. In this structure, the signal from one port (port 1) passes through a parabolic-shaped transmission line to N parallel ports (ports 2~→ ~N +1 ), which are positioned in a straight line at equal distances from each other. Due to diffraction, the traveling wave from port 1 will be cylindrical, and this parabolic-shaped transmission line converts the cylindrical wave into a plane wave at the N parallel ports. To accurately evaluate the performance of the divider/combiner, a new method is proposed by defining a parameter called S_{ error} . The simulated results obtained for a 1-to-4 divider/combiner within the frequency range of 15-60 GHz [120% bandwidth (BW)] indicate that the amplitude difference between ports is less than 2.4 dB, and the phase difference is less than 8°. To further enhance the amplitude and phase balancing, the shape of the transmission line, responsible for converting the cylindrical wave to a plane wave, is optimized using the particle swarm optimization (PSO) algorithm and simulation by MATLAB-HFSS API. The optimized results for a 1-to-4 divider/combiner within the frequency range of 15-60 GHz demonstrate an amplitude difference of less than 0.75 dB between the ports and a phase difference of less than 2.5°.